Abnormal expression of miRNA-21 and other miRNAs involved in polycystic ovary syndrome and the implications for public health especially in low- and middle-income countries - Khizar, Wafa; Hussain, Shahzad; Sarfraz, Bisma; Shahid, Eman; Ramdas, Nishana; Meyer, Johanna C; Godman, Brian (Journal of the Medical College for Women & Hospital, 2026)
Background: MicroRNAs are small non-coding RNA molecules crucial in regulating gene expression. In Polycystic Ovary Syndrome (PCOS), a common endocrine disorder in women of reproductive age, miRNA-21 and other miRNAs have been consistently reported as dysregulated, contributing to its pathophysiology. In PCOS, these are commonly altered (either raised or lowered) in ovarian cells and blood and this alteration can lead to the abnormal development of follicles, inflammation and hormone imbalance, which are major issues in PCOS. As a result, a potential biomarker for this condition that is associated with considerable morbidity. The development of potential biomarkers is important in developing countries such as Pakistan with high prevalence rates of up to 52% in Pakistani women of reproductive age as well as high co-payments impacting on seeking care. This is a key public health consideration in developing countries where multiple visits may be needed before a diagnosis of PCOS is made. Consequently, there is a need to consolidate current evidence to provide future direction. Materials and Method: A systematic review including studies showing that miRNA-21 and other miRNAs are involved in dysregulation in women with PCOS, including studies analyzing ovarian tissue and blood samples, and providing public health guidance building on co-author experience. Results: 52 studies were involved in the review. The dysregulation of miRNA-21 in PCOS is associated with altered hormonal levels, particularly elevated androgens, and insulin resistance. The overexpression of miRNA-21 is believed to contribute to metabolic disturbances commonly observed in PCOS patients. Overall, miRNAs have emerged as potential biomarkers for diagnosing PCOS due to their significant role in associate metabolic and hormonal alterations. Conclusion: The findings from this study provide valuable insights into the mechanisms of PCOS and the potential for miRNA-21as a biomarker and therapeutic target. This is crucial in developing countries such as Pakistan to address the challenges associated with diagnosing and managing PCOS. Other approaches are also needed to improve the mental health, and reduce morbidity, in this vulnerable group. J Med Coll Women Hosp.2026; 22(1): 188-220